Opportunistic relays selection for successive relaying with inter-relay interference - Liau, Q. Y. (Institute of Electrical and Electronics Engineers Inc., 2016)
In the presence of inter-relay interference, the capacity performance of successive relaying can be severely degraded. Existing literature on successive relaying does not consider the channel quality of the inter-relay channel in maximising the capacity performance. Therefore, we propose an opportunistic successive relaying scheme that jointly considers the channel conditions of source-to-relay channels, relay-to-destination channels and also the inter-relay channels. In the proposed scheme, we select a pair of relays out of N potential relays in a distributed fashion to optimise the instantaneous end-to-end capacity in the presence of inter-relay interference. The performance of the proposed opportunistic successive relaying scheme is simulated using Monte Carlo technique and the ergodic capacity is analysed. The simulation results justify that the proposed scheme is able to mitigate the adverse effect of inter-relay interference effectively. Based on the analytical result, we prove that the asymptotic ergodic capacity of the proposed scheme increases logarithmically with quadratic of the number of potential relays at high SNR.